Impact of subsurface crevassing on the depth-age relationship of high-Alpine ice cores extracted at Col du Dôme between 1994 and 2012 - Preunkert, Susanne; Bohleber, Pascal; Legrand, Michel; Gilbert, Adrien; Erhardt, Tobias; Purtschert, Roland; Zipf, Lars; Waldner, Astrid; McConnell, Joseph R.; Fischer, Hubertus (The Cryosphere, 2024)
Three seasonally resolved ice core records covering the 20th century were extracted in 1994, 2004, and 2012 at a nearly identical location from the Col du Dôme (4250 m above sea level, m a.s.l.; Mont Blanc, French Alps) drill site. Here, we complete and combine chemical records of major ions and radiometric measurements of 3H and 210Pb obtained from these three cores with a 3D ice flow model of the Col du Dôme glacier to investigate in detail the origin of discontinuities observed in the depth-age relation of the ice cores drilled in 2004 and 2012. Taking advantage of the granitic bedrock at Col du Dôme, which makes the ice core 210Pb records sensitive to the presence of upstream crevasses, and the fact that the depth-age disturbances are observed at depths for which absolute time markers are available, we draw an overall picture of a dynamic crevasse formation. This can explain the non-disturbed depth-age relation of the ice core drilled in 1994 and the perturbations observed in those drilled in 2004 and 2012. Since crevasses are common at high-Alpine glacier sites, our study points to the important need for rigorous investigations of the depth-age scale and glaciological conditions upstream of drill sites before interpreting high-alpine ice core records in terms of atmospheric changes.
Online veröffentlicht: 2. Mai 2024
Gesehen am 07.02.2025